Cooperative movement and prosperity across Italian regions - Michele Costa; Flavio Delbono; Francesco Linguiti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
Our main objective is exploring the association between widespread prosperity and the presence of the cooperative movement at the regional level in Italy between 2010 and 2019. We summarize the widespread prosperity through an index originally proposed by Sen (1976) and we then perform a panel regression showing that there is a positive and significant association between such an index and the presence of the cooperative movement as captured by the relative size of cooperative employees. We also detect that the cooperative movement contributes to the regional prosperity more through its employment than in terms of the added value it generates. Moreover, the size of the cooperative presence significantly concurs to explain some large differentials among Italian regions.
Keywords: I31; J54; 330; social cohesion; regional well-being; income inequality; resilience